2013
DOI: 10.2147/nrr.s39401
|View full text |Cite
|
Sign up to set email alerts
|

Risks associated with the use of morphine for analgesia: attitudes and perceptions amongst nursing students in French-speaking Switzerland

Abstract: Aims: This paper reports on the attitudes and perceptions of risks associated with the use of morphine for analgesia among nursing students and explores the relationship between those attitudes and perceptions and sociodemographic data. Background: Attitudes and perception of risks regarding the use of morphine for analgesia amongst nurses remain problematic, thus potentially leading to important consequences regarding the quality of pain management. Methods: A cross-sectional survey among 557 nursing-students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…The French version of the instrument was initially forward translated from Italian and then back-translated to ensure reliability of the statements. A first analysis [ 24 ] showed that two items, “It is necessary to evaluate pain (using a visual scale)” and ”The doctor must inform the patient when prescribing a drug/medicine containing morphine”, provided no information; hence, a 24-item instrument was developed and the current study is based on the 24-item French version. Also in this first analysis, of the questionnaire, the measured time to complete ranged between 20 and 25 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The French version of the instrument was initially forward translated from Italian and then back-translated to ensure reliability of the statements. A first analysis [ 24 ] showed that two items, “It is necessary to evaluate pain (using a visual scale)” and ”The doctor must inform the patient when prescribing a drug/medicine containing morphine”, provided no information; hence, a 24-item instrument was developed and the current study is based on the 24-item French version. Also in this first analysis, of the questionnaire, the measured time to complete ranged between 20 and 25 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these attitudes and beliefs have also been reported in other studies [ 19 - 22 ]. A Portuguese version has been applied among Portuguese health professionals of the Beira Interior region, South-East Portugal [ 12 , 23 ] and a French version was recently developed and applied among student nurses in French-speaking Switzerland [ 24 ]. This instrument was preferred because it was available in three different languages (Italian, Portuguese and French), which would theoretically allow comparisons between countries.…”
Section: Introductionmentioning
confidence: 99%
“…A French version of the questionnaire ("attitudes sur l'utilisation de la morphine") has been developed. 25 An initial analysis revealed two components, "morphine use and administration" and "risk perception." A more in-depth validation (Ferreira M, unpublished data, 2013) showed that the total number of items could be reduced to 19 without information loss, with a normalized Cronbach α of 0.741 for the shortened version (versus 0.700 for the original version).…”
Section: Questionnairementioning
confidence: 99%
“…4 Likewise, these drugs have also been related to negative side effects, such as excessive sedation, respiratory failure, urinary retention, or constipation, among others. 5 This situation along with social, cultural, and historical factors 6 has led to what is known as opiophobia, a set of inappropriate attitudes and beliefs regarding the deleterious effects of opioid administration for pain relief. 7 This has been related to reduced prescription of these drugs by health professionals and lower consumption by patients.…”
Section: Introductionmentioning
confidence: 99%